Prevalence of urinary schistosomiasis amongst primary school children in Ikwo and Ohaukwu Communities of Ebonyi State, Nigeria - Umoh, Nse O. (Afr J Lab Med, 2020)
BACKGROUND: Urinary schistosomiasis is a serious public health challenge in some communities of Ebonyi State, south-east Nigeria, partly resulting from a lack of adequate epidemiological data for the institution of effective control strategies. OBJECTIVE: This study evaluated the prevalence and risk factors of urinary schistosomiasis in rural communities of Ebonyi State, south-east Nigeria. METHODS: A total of 300 students, comprising 185 boys and 115 girls, were randomly selected for the study between July and December 2016. A questionnaire was administered to all participants to determine the risk factors for the disease in the area. Urine specimens collected from the participants were processed by sedimentation and examined microscopically for the eggs of Schistosoma haematobium. RESULTS: The overall prevalence rate for urinary schistosomiasis was 8.0%. Students aged 6–10 years had the highest prevalence of infection (10.3%). The prevalence was significantly higher amongst male students (10.3%; p = 0.038) compared with female students (4.4%). Logistic regression analysis showed a significant association between schistosomiasis infection and freshwater contact activities (p = 0.007; odds ratio = 1.89; 95% confidence interval: 4.33–16.17). Contact with stream, pond, river and well water were associated with infection rates of 25%, 14%, 5.3%, and 4.4%, respectively. CONCLUSION: A relatively low prevalence of urinary schistosomiasis was found in the area. Participants’ socio-economic status and dependence on contaminated water sources were core modifiable risk factors. Health education and development of potable water infrastructure, amongst other interventions, would likely reduce the burden and transmission of urinary schistosomiasis in this locality.